Key access and utilization descriptors for finger millet genetic resources - Bioversity International; India Coordinated Research Project on Small Millets; International Institute of Tropical Agriculture; International Crops Research Institute for the Semi-Arid Tropics; National Bureau of Plant Genetic Resources (2010)
This minimum list consists of an initial set of characterization and evaluation descriptors for finger millet utilization